Hyperparasitic Fungi on Black Mildews (Meliolales, Ascomycota): Hidden Fungal Diversity in the Tropics - Bermúdez-Cova, Miguel A.; Cruz-Laufer, Armando J.; Piepenbring, Meike (Frontiers in Fungal Biology, 2022)
Hyperparasitism on plant-parasitic fungi is a widespread but rarely studied phenomenon. Here, for the first time, we compile in a checklist information provided by peer-reviewed literature for fungi growing on colonies of black mildews (Meliolales, Ascomycota), a species-rich group of tropical and subtropical plant-parasitic microfungi. The checklist contains information on 189 species of contact-biotrophic microfungi in 82 genera. They belong to seven morphological groups: dematiaceous hyphomycetes, moniliaceous hyphomycetes, pycnidioid, perithecioid, catathecioid, and apothecioid fungi. By the fact that species accumulation curves do not reach saturation for any tropical country, it is evident that the knowledge of the diversity of hyperparasitic fungi on Meliolales is incomplete. A network analysis of records of hyperparasitic fungi, their host fungi and host plants shows that genera of hyperparasitic fungi are generalists concerning genera of Meliolales. However, most species of hyperparasitic fungi are restricted to meliolalean hosts. In addition to hyperparasitic fungi, diverse further microorganisms use meliolalean colonies as ecological niche. Systematic positions of most species are unknown because DNA sequence data are lacking for species of fungi hyperparasitic on Meliolales. We discuss the specific challenges of obtaining DNA sequence data from hyperparasitic fungi. In order to better understand the diversity, evolution and biology of hyperparasitic fungi, it is necessary to increase sampling efforts and to undertake further morphological, molecular, and ecological studies.